Improving rate of decline of FEV(1) in young adults with cystic fibrosis - Que, C (BMJ Group, 2006)
BACKGROUND: CF is characterised by a progressive decline in lung function; reductions in this decline are often used as a measure of success in clinical trials. With improvements in treatment it may be that there has been a temporal shift in the pattern of the disease. METHODS: 318 patients born in five successive cohorts and attending a specialist clinic with at least two routine measurements of lung function made between the ages of 18 and 22 were included. The declines in their lung function were estimated and compared. RESULTS: The mean (SE) slopes for percentage predicted forced expiratory volume in 1 second (FEV(1)) and forced vital capacity (FVC) were −1.53 (0.36)% and −1.27 (0.34)%, respectively (NS). The annual deterioration in FEV(1) was −2.49%, −1.99% −2.20%, −1.65%, and −0.65% from the earliest to the most recent birth cohort; a similar pattern was observed for changes in FVC. There were no differences between male and female patients. Patients infected with Pseudomonas had a greater average decline in FEV(1) (−1.6% v −1.1%). CONCLUSIONS: The rates of decline in lung function in young adults with CF have diminished with successive birth cohorts. This has important implications for the design of clinical studies in this disease.